Performance evaluation of a solar-powered thermoelectric cool box with GSM-IoT monitoring for coastal fisheries - Shaffa Shaffa; RD Kusumanto; Ahmad Taqwa (Politeknik Negeri Lhokseumawe, 2026)
This study develops and evaluates an autonomous solar-powered cool box to improve the storage quality of fishermen catch in the Sungsang Estuary, where limited access to ice and electricity accelerates fish deterioration. The system integrates a monocrystalline photovoltaic panel, VRLA battery, MPPT charge controller, thermoelectric cooling module, automatic solar tracking, and GSM-IoT monitoring for remote operation. Solar tracking uses LDR sensors and a wiper motor to continuously adjust panel orientation for improved solar energy capture. A 14-day field test in a maritime environment showed a maximum power output of 199.9 W and an average daily energy yield of 1,285.6 Wh. The generated energy sustained the cooling load while maintaining system voltage between 22.35 and 23.55 V under varying irradiance. Panel tilt adjustment from -30° to +32° improved solar radiation absorption throughout the day. The cool box maintained an average internal temperature of 6-8°C, with occasional short-term increases to 14-15°C caused by external ambient conditions. The results demonstrate that integrating photovoltaic power, automatic tracking, and GSM-IoT monitoring provides a practical renewable-energy solution for cold storage, digitalization, and sustainability in small-scale fisheries.